Open data: Examining experienced lateralization of sounds over headphones with electroencephalography - Wiens, Stefan; Greiciute, Mingaile; Gerdfeldter, Billy (Stockholm University, 2025)
Supplementary material for the associated publication.

ABSTRACT

In the search for the neural correlates of auditory consciousness, a candidate has been found using electroencephalography: the auditory awareness negativity (AAN). Earlier studies have investigated the AAN in response to lateralized sound. With headphones, there is a clear lateralization of AAN when two auditory lateralization cues are combined: the interaural level difference (ILD) and interaural time difference (ITD). To separate the contribution of these cues to a lateralized AAN, we tested three stimulus conditions with headphones: A combination of ILD and ITD, solely ITD, and monaural stimulation. Results suggest that ILD and ITD are required in conjunction for a lateralized AAN, and neither ITD nor monaural stimulation can yield a lateralized AAN. These results suggest that event-related potentials may be limited in measuring the lateralization of the neural correlates of auditory consciousness to lateralized sounds, depending on auditory cues and acoustic environment.

ETHICS STATEMENT

Ethical review and approval were not required for studying human subjects in accordance with local law and institutional requirements, as we did not collect personal and biological data that can be traced back to the subject. The experiment adhered to the declaration of Helsinki. Subjects were required to provide their written informed consent to participate in this study and that their raw data will be shared in anonymized form.

The uploaded data are considered anonymized because there is no key that links test subjects to their data.

DATE & LOCATION OF DATA COLLECTION

The study comprised two experiments. Subjects for experiment 1 (N = 32; Final sample: N = 31) were tested between November 2023 and February 2024 at the Department of Psychology, Campus Albano, Stockholm, Sweden. Subjects for experiment 2 (N = 44; Final sample: N = 40) were tested between February 2024 and May 2024 at the Department of Psychology, Campus Albano, Stockholm, Sweden.

DATA & FILE OVERVIEW

The files contain the raw data, scripts, and results of main and supplementary analyses of the electroencephalography (EEG) study reported in the main publication.

!NB! In the figures and analysis scripts, experiment 1 is called AAN_ITD, and experiment 2 is called AAN_MONO. Within experiment 1, the ILD+ITD condition is called “control.”

File Structure

The supplementary materials are organized by experiment/analysis within the study. At the top level there is one Readme.pdf file and three main folders:

* Eklund_Reanalysis: Contains all material regarding the reanalysis of Eklund et al (2021).

* Experiment 1: Contains all material, including figures, regarding experiment 1.

* Experiment 2: Contains all material, including figures, regarding experiment 2.

Main Results

For results, ERPs, and topoplots, see folders Experiment_1 and Experiment_2. The folders are identical in structure, containing:

+ Analysis files, in .html-format, with all results and statistical models separated by AAN and LP. These files are created using Quarto in R, and contain code snippets to all available results, to allow for transparency into analyses.

+ ERPs of grand averages of AAN and LP.

+ Topographical plots of grand averages of AAN and LP.

Folder Experiment_2 additionally contains files regarding comparative analyses between experiment 1 and 2:

+ Analysis_Comparison_AAN.html for comparison of AAN between experiments.

+ Analysis_Comparison_LP.html for comparison of LP between experiments.

Raw Data and Scripts for Experiment and Analysis

For raw data and scripts, see folders Experiment_1 and Experiment_2 for supplementary files regarding experiment 1 and experiment 2, respectively. Within these folders, see the zipped raw data files. The structure of these folders is identical. Within these folders, see:

+ Data folder for raw .bdf-files and corresponding logfiles.

+ Mne folder for scripts of MNE-python for processing EEG-data.

++ Preprocess.py preprocesses the raw EEG files and applies ICA.

++ Analysis_epoch constructs the figures.

++ Results folder contains ERPs separately per subject and grand averages.

+ Psychopy folder for scripts to run the experiments.

++ Exp_AAN_ITD.py runs experiment 1.

++ Exp_AAN_MONO.py runs experiment 2.

++ Settings.tsv sets, and logs, staircasing and behavioral results.

++ The rest are supporting files used by our lab.

+ R folder for scripts to analyze the data.

++ Raw code in steps (numbered 1, 2, 3) to compute and analyze models.

+++ For comprehensive summary with code snippets, see Analysis (.html) files above, in folders Experiment_1 and Experiment_2.

++ For results, and Bayesian models, see results-subfolder:

+++ Subfolder figures contains mean amplitude plots (such as figure 1 and 2, published in the article).

Reanalysis of Eklund et al (2021)

For reanalyzed data from Eklund et al. (2021), see folder Eklund_Reanalysis:

+ reanalysis_AAN_Eklund_2021.html for reanalyzed AAN.

+ reanalysis_LP_Eklund_2021.html for reanalyzed LP.

+ For raw data and scripts of the reanalysis, see Eklund_reanalysis_raw_data.zip
Keywords: Psychophysiology; Cognitive neuroscience; Sensory processes, perception and performance; Neurosciences; Neurovetenskaper; Psychology; Psykologi